The Poetry of Cao Zhi - Cutter, Robert Joe; Kroll, Paul W.; Kroll, Paul W. (Berlin/Boston De Gruyter, 2021)
This is the first complete translation of the poetry of Cao Zhi, a major figure from the formative age of classical Chinese poetry. The translations take the reader beyond anthology pieces to present a more complete view of the literary practices and concerns of Cao Zhi and his contemporaries. A number of works not previously available in English are included here, enhancing our understanding of the culture of China$1 (Bs early medieval period.s
English
Chinese
Keywords: Language; Literature: history & criticism; Regional studies; Cao Zhi; Jian$1 (Bans; Early Medieval Chinese Poetry; Chinese Literature